1986
DOI: 10.1016/0304-3959(86)90211-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of changes in myofascial trigger point sensitivity with the pressure algometer following passive stretch

Abstract: In order to determine the relationship between trigger point sensitivity and the referred symptoms of myofascial pain, VAS ratings of referred pain intensity and pressure algometer measures of myofascial trigger point sensitivity were taken pre and post treatment of the muscle containing the trigger point with passive stretch. The results in 20 subjects, experiencing unilateral or bilateral myofascial head and neck pain, showed that myofascial trigger point sensitivity decreases in response to passive stretch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
11

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(70 citation statements)
references
References 4 publications
3
56
0
11
Order By: Relevance
“…The pressure pain threshold (PPT) for the examination of MTPs is the minimal force that induces pain. [6][7][8][9] Infrared thermography is a non-ionizing and noninvasive imaging technique that detects the distribution of body surface heat. It detects, records and transforms into images the infrared radiation emitted by the human skin, reflecting in real-time the microcirculatory dynamic of the cutaneous surface of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…The pressure pain threshold (PPT) for the examination of MTPs is the minimal force that induces pain. [6][7][8][9] Infrared thermography is a non-ionizing and noninvasive imaging technique that detects the distribution of body surface heat. It detects, records and transforms into images the infrared radiation emitted by the human skin, reflecting in real-time the microcirculatory dynamic of the cutaneous surface of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed to date have shown that in MPS, the use of an algometer is safe in terms of determining the tenderness of the trigger points. [16][17][18][19] The second investigator identified the patient groups using the RAS system. If the patient was in the oral flurbiprofen group, the tablets were given to the patients along with an explanation of how and when to take them, and if the patient was in one of the needling groups, the procedures were performed by the second investigator.…”
Section: Methodsmentioning
confidence: 99%
“…The results are still controversial. Some studies have reported significant improvement through use of STR in combination with other modalities as a part of MTrP treatment [12][13][14][15][16] . The combination treatment has been proved to be effective in treating MTrP rather than STR alone 14,16) .…”
Section: Introductionmentioning
confidence: 99%